Answer:
x = 10
EF = 10
FG = 26
Step-by-step explanation:
Given the following data;
Point EF = 2x - 20
Point FG = 3x-19
Straight line, EG = 26
It can be deducted that the points are on a straight line, EG.
Therefore, EG = EF + FG
Substituting the values into the equation, we have;
26 = 2x - 20 + 3x - 19
Rearranging the equation, we have;
26 + 20 + 19 = 2x + 3x
75 = 5x
x = 75/5
x = 15
To find point EF;
EF = 2x - 20
Substituting the value of "x" into the equation;
EF = 2(15) - 20
EF = 30 - 20
EF = 10
To find point FG;
FG = 3x - 19
Substituting the value of "x" into the equation;
FG = 3(15) - 19
FG = 45 - 19
FG = 26